2015
DOI: 10.1371/journal.pone.0142221
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Transcriptome Analysis of Cucumber and Botrytis cinerea during Infection

Abstract: Cucumber gray mold caused by Botrytis cinerea is considered one of the most serious cucumber diseases. With the advent of Hi-seq technology, it is possible to study the plant–pathogen interaction at the transcriptome level. To the best of our knowledge, this is the first application of RNA-seq to identify cucumber and B. cinerea differentially expressed genes (DEGs) before and after the plant–pathogen interaction. In total, 248,908,688 raw reads were generated; after removing low-quality reads and those contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 42 publications
4
45
0
Order By: Relevance
“…DEGs were detected and 621 and 297 DEGs were up-regulated and down-regulated, respectively ( Figure S1b, and Tables S5 and S6). Our gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses of tomato and B. cinerea DEGs revealed that the enriched GO terms (Figure S1c,d,and Tables S7 and S8) and KEGG pathways ( Figure S2, and Tables S9 and S10) of the DEGs were similar to those previously reported (De Cremer et al, 2013;Kong et al, 2015;Rezzonico et al, 2017).…”
Section: Degs In Tomato and B Cinerea At The Early Interacting Stasupporting
confidence: 83%
See 1 more Smart Citation
“…DEGs were detected and 621 and 297 DEGs were up-regulated and down-regulated, respectively ( Figure S1b, and Tables S5 and S6). Our gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses of tomato and B. cinerea DEGs revealed that the enriched GO terms (Figure S1c,d,and Tables S7 and S8) and KEGG pathways ( Figure S2, and Tables S9 and S10) of the DEGs were similar to those previously reported (De Cremer et al, 2013;Kong et al, 2015;Rezzonico et al, 2017).…”
Section: Degs In Tomato and B Cinerea At The Early Interacting Stasupporting
confidence: 83%
“…In B. cinerea pathosystems, host plant and/or pathogen transcriptomes have been investigated in Arabidopsis (Mulema and Denby, 2012), tomato (Blanco-Ulate et al, 2013;Smith et al, 2014;Vega et al, 2015;Rezzonico et al, 2017), lettuce (De Cremer et al, 2013), and cucumber (Kong et al, 2015). These reports greatly increase our understanding of the mechanisms underlying B. cinerea interaction with its diverse hosts.…”
Section: Introductionmentioning
confidence: 99%
“…This difference was somewhat expected as it was apparent from the phenotypic observations that the fungal biomass at earlier stages was smaller compared to that at later stages (Fig 1a). Lower percentage of alignments at earlier phases of infection have also been observed in other pathogen-host interactions [34,54,55]. PCA results indicated that the differences in gene expression due to variability between replicates were small (9.15%, PC3, data not shown) compared to sample type (in vitro vs. in planta, PC1 63.1%) and time of sampling (T1 vs T2, PC2 15.4%) ( Fig 2).…”
Section: Plos Onesupporting
confidence: 58%
“…The JA pathway plays important roles in defense against necrotrophic pathogens in various plants (Penninckx et al, 1998;Vijayan et al, 1998;Kong et al, 2015;Jia et al, 2016;Lecompte et al, 2017;He et al, 2018). JA biosynthesis begins with the release of a-linolenic acid from membrane lipids in the chloroplast (Wasternack and Hause, 2013).…”
Section: Introductionmentioning
confidence: 99%